Serological evidence of antibodies to Flaviviridae in wild birds in Portugal - Filipa Loureiro; Luís Cardoso; Ana C. Matos; Cristina Pintado; Filipe Silva; Mariana Ferreira; Ricardo Brandão; Carolina Lopes; Ana Patrícia Lopes; João Rodrigo Mesquita; Manuela Matos; Ana Cláudia Coelho (BMC, 2024)
Abstract Emerging infectious diseases are a major threat to biodiversity and an important public health issue. Flaviviruses are the cause of several emerging vector-borne zoonotic arboviruses whose distribution is currently increasing in Europe. The evidence that West Nile virus (WNV) circulates in resident and migratory species has implications for both animal and public health and should therefore be studied in depth. USUTU (USUV), Bagaza (BAGV) and tick-borne encephalitis virus (TBEV) are other viruses that are beginning to spread more widely. An integrated surveillance program, namely in birds, is essential for reducing the risk of infection in human populations within the One Health principles. In the present study, wild birds admitted to wildlife rehabilitation centers in Portugal were sampled. Two hundred eight blood samples were assayed serologically for antibodies to flaviviruses by using a commercial ELISA kit. An overall seroprevalence of 19.6% (95% confidence interval [CI]: 13.7-26.7%) was observed. Antibodies against flaviviruses were detected in 13 (35.1%) different species of wild birds. Accipitriformes (26.7%; 95% CI: 18.5-36.2%) and Strigiformes (26.7%; 95% CI: 14.6-42.0%) were the orders with the highest seroprevalence rates recorded. There were no statistically significant differences (p = 0.725) between the geographical regions (NUTS II) studied, but a statistically significant difference (p = 0.017) was found between sex (male: 34.4%; female: 4.8%). A higher seroprevalence was detected in adults (32.1%) than in juvenile birds (9.3%) (p = 0.014), and age was considered a risk factor for flavivirus infection in wild birds (odds ratio 1.4; 95% CI: 0.5-4.0). More epidemiological studies are needed in Portugal since the actual spread of the genus Flavivirus throughout the country is unknown.